OROLNI QUTQARISh XALQARO JAMGʻARMASI: TAShKIL ETILIShI VA FAOLIYATI - Abatov, A.R. (SCIENCE and SOCIETY, 2025)
This article is about the International Fund for Saving the Aral Sea, an international organization that plays a key role in solving acute problems facing the residents of the Aral Sea region. Issues related to the creation and operation of the International Fund for Saving the Aral Sea, ongoing projects, and current issues facing the fund are also discussed.
Keywords: The Aral Sea problem; IFAS; ecology; environment; international organizations; projects; nature; factor; effective cooperation; population of the Aral Sea region